PANDANGAN TOKOH MASYARAKAT TERHADAP PERNIKAHAN DI BULAN SURO TINJAUAN HUKUM ISLAM: Studi Kasus di Desa Dragan Kecamatan Tamansari Kabupaten Boyolali - Malik Hidayat, Nabil; Masrokhin; Faruq, Ahmad (Irtifaq, 2025)
People in Dragan Village avoid getting married in the month of Suro because it is said to bring bad luck. The overall objective of this study is to study how religious and political leaders view marriage in the month of Suro according to Islamic law. A qualitative, normative research strategy was used for this research. The next step is to collect data by conducting interviews and keeping notes in the field. According to research findings, marriages in the month of Suro originate from the desire to uphold ancestral customs. The results of the urf assessment include urf authentic if the motivation is only to avoid doubts and caution in getting married, but urf fasid if he feels that getting married in the month of Suro can bring disaster to the bride and groom.